2022
DOI: 10.3389/fmars.2022.864801
|View full text |Cite
|
Sign up to set email alerts
|

Calcification, Dissolution and Test Properties of Modern Planktonic Foraminifera From the Central Atlantic Ocean

Abstract: The mass of well-preserved calcite in planktonic foraminifera shells provides an indication of the calcification potential of the surface ocean. Here we report the shell weight of 8 different abundant planktonic foraminifera species from a set of core-to sediments along the Mid-Atlantic Ridge. The analyses showed that near the equator, foraminifera shells of equivalent size weigh on average 1/3 less than those from the middle latitudes. The carbonate preservation state of the samples was assessed by high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Their high abundance is the result of the dominance of this group of foraminifera during the sedimentation [24] , when the inhabitants of the mixed layers ( Acarinina sp., Morozovella sp.,) were less abundant. In addition, it is known that foraminifera that are surface dwellers are much more susceptible to dissolution, which may also be the reason why acarininids and morozovellas were present in very low numbers [25] .…”
Section: Methods Validationmentioning
confidence: 99%
“…Their high abundance is the result of the dominance of this group of foraminifera during the sedimentation [24] , when the inhabitants of the mixed layers ( Acarinina sp., Morozovella sp.,) were less abundant. In addition, it is known that foraminifera that are surface dwellers are much more susceptible to dissolution, which may also be the reason why acarininids and morozovellas were present in very low numbers [25] .…”
Section: Methods Validationmentioning
confidence: 99%
“…6.023x10 23 molecules), equivalent to ppmv. However, the idea of a heterogeneous mole of air made up of a total of 6.022x10 23 different molecules is not useful in thermodynamic terms. The mean partial pressure (pi) of each gas per molecule can be given in terms of its number density (N) and the temperature (T).…”
Section: Chemistry Of Co2 In Seawatermentioning
confidence: 99%
“…The thermodynamic stoichiometry of reactions ( 7) and ( 8) may be questioned, although the overall reaction favoring emission of CO2 is qualitatively correct. Recent data from Zarkogiannis et al [23] showed that planktonic foraminifera from the central Atlantic Ocean had larger, denser shells in cooler water compared to tropical, possible a result of reduced competition for calcification.…”
Section: K Omentioning
confidence: 99%
“…The application of µCT for estimating the carbonate solubility and calcification capacity of marine calcareous materials has recently been widely discussed (Johnstone et al, 2010;Iwasaki et al, 2015;2019a;Todd et al, 2020;Zarkogiannis et al, 2020;Kinoshita et al, 2021;Kuroyanagi et al, 2021;Ofstad et al, 2021;Charrieau et al, 2022). Furthermore, ambitious attempts have been made to estimate the concentration of carbonate ions in past seawater by quantifying the dissolution of foraminifera tests (e.g., Iwasaki et al, 2019b;, habitat depth (Zarkogiannis et al, 2022), and to detect the biological effects of anthropogenic environmental changes since the Industrial Revolution (Fox et al, 2020).…”
Section: Introductionmentioning
confidence: 99%